Enhancing Student Character through Effective Curriculum Quality Management for Special Needs Education - Saniputri, Regina Maheswari; Purnamasari, Feny Afifah; Nurdiana, Irfan Intan; Rahayu, Diah Daniswara; Suwandari, Lilis (Journal of Educational Management Research, 2025)
Character education in special schools is vital for developing students' personality, independence, and social skills. However, the 2024 Education Report Card indicates that student character development and curriculum management remain at the medium and developmental stages, suggesting a gap between ideal education goals and actual implementation. This study explores the application of the PDCA (Plan-Do-Check-Act) quality management cycle in managing the character curriculum. Using a qualitative case study approach, the research involved in-depth interviews, participatory observation, and document analysis. Findings reveal that the Plan stage is collaboratively and adaptively implemented through a thematic approach with teachers and parents. The Do stage focuses on instilling character values through practice and teacher role modeling. The Check stage involves reflective supervision and ongoing evaluations, while the Act stage emphasizes internal teacher training and curriculum revisions based on field data. The PDCA cycle has proven effective in creating a responsive, reflective, and sustainable character curriculum system. This study provides valuable insights for special education institutions aiming to develop a more effective and context-specific curriculum management system.